Protein Composition of Mycobacterium smegmatis Differs Significantly Between Active Cells and Dormant Cells With Ovoid Morphology - Trutneva, Kseniya; Shleeva, Margarita; Nikitushkin, Vadim; Demina, Galina; Kaprelyants, Arseny (Frontiers in Microbiology, 2018)
Mycobacteria are able to form dormant cells, which survive for a long time without multiplication. The molecular mechanisms behind prolonged survival of dormant cells are not fully described. In particular, little information is known on biochemical processes which might take place in cells under dormancy. To gain insight into this problem, Mycobacterium smegmatis cells in deep dormant state were obtained after gradual acidification of the growth medium in prolonged stationary phase followed by one month of storage at room temperature. Such cells were characterized by low metabolic activity, including respiration, resistance to antibiotics and altered morphology. The protein composition of cytoplasm and membrane fractions obtained from active and dormant cells were compared by 2D electrophoresis. Almost half of the proteins found in the proteome of dormant cells were absent in that of active cells. This result differs significantly from published results obtained in other studies employing different models of mycobacterium dormancy. This discrepancy could be explained by a deeper dormancy developed in the present model. A feature of a “dormant proteome” is high representation of enzymes involved in glycolysis and. defence systems that inactivate or detoxify reactive oxygen and nitrogen species, aldehydes and oxidized lipids. Dormant mycobacteria are enriched by degradative enzymes, which could eliminate damaged molecules, or the products of such degradation could be reutilized by the cell during prolonged storage. We suggest that some enzymes in dormant cells are inactive, having been used upon transition to the dormant state, or proteins stored in dormant cells for further cell reactivation. At the same time, some proteins could be functional and play roles in maintenance of cell metabolism, albeit at a very slow rate. This study provides a clue as to which biochemical processes could be active under dormancy to ensure long-term viability of dormant mycobacteria.